Evaluation of the efficacy of biological agents used to treat Dress Syndrome refractory to corticosteroids: A scoping review (Research, Society and Development, 2025)
Patients with Dress Syndrome often present resistance to traditional pharmacological therapies, which include the use of corticosteroids and pulse therapy. In severe and recurrent cases of this syndrome, the use of biological agents tends to be strongly recommended, allowing the prevention of possible deleterious outcomes. The present study aims to evaluate the efficacy of biological agents used for Dress Syndrome refractory to corticotherapy. For this scoping review, carried out through the PubMed and ScienceDirect platforms, between the years 2022 and 2025, the descriptors chosen were ‘’Drug Hypersensitivity Syndrome’’, ‘’Biological Products’’ and ‘’Adverse Drug Event’’. The inclusion criteria consisted of (1) Evaluation of the use and efficiency of biological agents, (2) Analysis of the management of Dress Syndrome refractory to corticosteroid therapy, (3) Studies comparing the performance of different immunobiological agents, (4) Texts addressing monitoring, follow-up and clinical management and (5) Articles in English and Portuguese. The exclusion criteria consisted of inappropriateness to the topic, case reports, editorials, studies with animals and texts outside the time limit. Patients with severe Dress who used biological agents early showed a reduction in acute lethal symptoms, as well as a reduction in the length of hospital stay and deleterious outcomes associated with high doses of corticosteroids. The studies demonstrated that compared to the elderly population, young individuals tend to have a better prognosis and therapeutic response. Recommendations regarding the interaction and discontinuation of such biological therapies are controversial topics to be elucidated through new studies.